Green Earth: Carbon Emissions, ISO 14001, Governance Structures, Militarily Connected from the Manufacturing Industries in Indonesia - Sri Iswati; Pikar Setiawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: This study aims to examine the effect of ISO 14001 empirically, Governance Structures and companies led by back with a military to carbon emissions disclosure in the manufacturing company that registered at the (IDX) Indonesian Stock Exchange of 2013 to 2017.Design/Methodology/Approach: The sample in this research was 53 companies chosen based on purposive sampling technique. The data used was 265 observation. The testing of hypotheses uses Ordinary Least Square (OLS) regression with STATA v14.Research findings: The research results show that there are three variables have proven to be not significant to carbon emissions, namely board independent, military connection, and return of equity. Research proves that board independent, military relationship, and return of equity did not affect commitment to express carbon emissions. On the other hand, this research demonstrates that there is four a variable that has significant impact on the carbon emission disclosure in manufacturing company that is, board size, ISO 14001, firms size and leverage.Theoretical contribution/ Originality: This research explain that the average Carbon Emission Disclosure (CED) performance of companies that have military-connected is higher than companies that not military-connected. Companies that have an ISO 14001 certificate with military connections have a higher average and are significantly higher than companies that are not connected with the military.Practitioner/Policy implication: The results of this study indicate the importance for companies to pay attention to the environment of production activities and the need for the government to set standards for disclosure of carbon emissions in order to achieve clean.Research limitation/Implication: The research carried out is still limited to companies that publish carbon emissions disclosures, inconsistent and still relatively low because disclosure of carbon emissions is still voluntary.